2010
DOI: 10.1007/s11356-010-0392-1
|View full text |Cite
|
Sign up to set email alerts
|

Applications of polychlorinated biphenyls

Abstract: A major contribution of this paper is to differentiate reported commercial applications of PCBs that can be documented from those which cannot. Undocumented uses may include actual minor uses as well as reported applications that are unlikely ever to have been commercialized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
214
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(231 citation statements)
references
References 22 publications
(17 reference statements)
1
214
0
7
Order By: Relevance
“…Maroni et al [105] reported the hepatotoxicity of VCM and other studies have shown the capacity of VCM to Group 1 [76] TCE 79-01-6 Dry cleaning; paint stripping; metal degreasing; production of chlorinated chemical compounds; shoe manufacturing; aircraft/aerospace, electronics and printing industry [125,127] Group 1 [129] PCE 127-18-4 Dry cleaning; textile processing; metal degreasing [138] Group 2A [129] DDT 50-29-3 Farming industry [141,145] Group 2B [148] N-nitrosamines 35576-91-1 Plastic, rubber and pharmacological manufacturing; farming industry; metalworking; electrical component production and use; gasoline and lubricant additives, production and use [159][160][161][162][163][164][165] Group [160,161] TCDD 1746-01-6 Waste management; paper mill; timber manufacturing; iron and steel manufacturing; electric power industry [175,179] Group 1 [76] PeCDF 57117-31-4 Cement and metalworking industry; chemical manufacturing [171,172,175] Group 1 [76] PCB 1336-36-3 Electrical industry, plastic and chemical industry; maintenance/repair technicians of PCB devices [175,[186][187][188][189][190] 1 Group [76,207] PBB Electronics recycling industry; maintenance/repair technicians of PBB devices [209][210][211][212] Group 2A [207] Chloral 75-87-6 Insecticides and herbicide production; p...…”
Section: Organic Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maroni et al [105] reported the hepatotoxicity of VCM and other studies have shown the capacity of VCM to Group 1 [76] TCE 79-01-6 Dry cleaning; paint stripping; metal degreasing; production of chlorinated chemical compounds; shoe manufacturing; aircraft/aerospace, electronics and printing industry [125,127] Group 1 [129] PCE 127-18-4 Dry cleaning; textile processing; metal degreasing [138] Group 2A [129] DDT 50-29-3 Farming industry [141,145] Group 2B [148] N-nitrosamines 35576-91-1 Plastic, rubber and pharmacological manufacturing; farming industry; metalworking; electrical component production and use; gasoline and lubricant additives, production and use [159][160][161][162][163][164][165] Group [160,161] TCDD 1746-01-6 Waste management; paper mill; timber manufacturing; iron and steel manufacturing; electric power industry [175,179] Group 1 [76] PeCDF 57117-31-4 Cement and metalworking industry; chemical manufacturing [171,172,175] Group 1 [76] PCB 1336-36-3 Electrical industry, plastic and chemical industry; maintenance/repair technicians of PCB devices [175,[186][187][188][189][190] 1 Group [76,207] PBB Electronics recycling industry; maintenance/repair technicians of PBB devices [209][210][211][212] Group 2A [207] Chloral 75-87-6 Insecticides and herbicide production; p...…”
Section: Organic Solventsmentioning
confidence: 99%
“…In one case, exposure to olive oil accidentally contaminated with PCB resulted in death from hepatic cirrhosis. Other studies in workers exposed to the PCB have reported an increased incidence of liver tumors [185][186][187][188] . Some possible mechanisms by which PCB can cause cancer have been assumed: Reactive oxygen species (ROS) is produced through the enzymatic oxidation or autoxidation of PCB; PCB determines the increased expression of genes responsible for inflammation and apoptosis in the liver; and PCB has "toxic" effects on certain genes, such as the loss of part of a chromosome and chromosome breakage [189][190][191][192][193][194][195][196][197][198][199] .…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%
“…PCBs were mainly used worldwide between 1930s and 1970s as complex mixtures, such as Aroclor in electrical transformers and capacitors, heat transfer systems, paints, coatings, and flame retardants because of their relatively low flammability and excellent dielectric properties (Erickson and Kaley, 2011). Despite their ban in the late 1970s, PCBs continue to be recorded as one of the major contaminants worldwide due to their properties and release from atmospheric deposition, surface runoff from industrial wastewater discharge, and from municipal waste sites in the environment (Lana et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The required properties of electrical insulating fluids are high dielectric strength, low viscosity, high chemical stability and etc. Polychlorinated Biphenyls (PCB) fit those criteria, therefore they were widely used as dielectric fluid in transformers from 1930 [8]. PCBs (C 12 H 10-n Cl n ) are the family of chemicals formed by attaching one or more chlorine atoms to a pair of connected benzene rings.…”
Section: Ecological Approachmentioning
confidence: 99%